Editorial - Cataldo Neto, Alfredo; Gomes, Irenio; Engroff, Paula; Crippa, Anelise; Bisol, Luísa Weber; Loureiro, Fernanda; Sgnaolin, Vanessa; Lessa, Adriana da Silva (PAJAR - Pan-American Journal of Aging Research, 2016)
.